The Role of Status Consumption and Materialism in Influencing Attitude towards Counterfeit Fashion Product - Mazli, Mohadzlishah bin; Ishak, Mohd Fikri bin; Muhamed, Ariff Azly bin (Information Management and Business Review, 2023)
The act of counterfeiting spans across various industries and the impact can be seen beyond economic factors. In consumer behavior, the impact of status consumption and materialism has influenced purchase decisions in which consumption is not only based on how it makes an individual feel but also on those around them. Ultimately, the extent to which consumers may go in terms of getting status recognition influenced them to look for “cheaper” alternatives to genuine manufactured products. Hence the demand for counterfeit fashion products kept rising over the years. This research shows the impact of materialism and status consumption in influencing consumer attitudes toward counterfeit fashion products. Data were analyzed using a partial least square (PLS) approach to structural equation modeling (SEM). Materialism is significant in influencing attitude whereas there was no significant relationship found between status consumption and attitude.